A Study of the Mechanism and Kinetics of the Synthesis of Methanol and Higher Alcohols Over Alkali Promoted Copper/Zinc-Oxide/Chromia Catalysts - Calverley, Michael Edward (My University, 1989)
Methanol and higher alcohols are produced when mixtures of CO, CO₂ and H₂ are reacted over Cu/ZnO catalysts at temperatures above about 250°C and pressures of 5 to 10 MPa. Relatively little is known about the synthesis of this mixed alcohol product, which has potential usefulness as a liquid fuel, or as a non-lead octane improver for gasoline. In the present work, various aspects of the synthesis of methanol and higher alcohols over Cu/ZnO/Cr₂O₃ catalysts have been investigated.
Addition of ¹³C labelled methanol to the reactor feed gas showed that methanol is incorporated directly into the higher alcohol product. Enrichment patterns of ¹³C in the higher alcohols suggested that CO is also a direct precursor of C₁ intermediates which produce higher alcohols.
A kinetic model of the higher alcohol synthesis (HAS), derived on the basis of direct mechanistic information, has not been reported. In the present work, the kinetics of the HAS have been successfully modelled by a scheme in which CH₃OH, CO, and CO₂ are converted directly into higher alcohols. The model was found to be consistent with the kinetic observations made for a wide range of reactor operating conditions including: H₂/(CO+CO₂) ratios of 0.36 to 1.8, CO₂/CO ratios of 0 to 1.35, CH₃OH feed concentrations of 0 to 5.3 percent, for (CO+H₂) conversions of 3.5 to 18 percent and at total pressures ranging from 5 to 10 MPa.
The kinetic observations of the methanol synthesis, made under the same operating conditions, were well described by a model based on the assumption that methanol is formed from both CO and CO₂ in parallel reactions, on different catalytic sites. This model is unique in that it is consistent with the most recent mechanistic and kinetic observations of other workers, and in that it describes the methanol synthesis behaviour at conditions suitable for the HAS.
Similarities between the methanol and higher alcohol synthesis models suggest that sites which convert CO to methanol also convert CO to higher alcohols, while sites that convert CO₂ to methanol also convert CO₂ to higher alcohols. Experiments with catalysts promoted with various amounts of K₂CO₃ promoter suggest that CO conversion is associated with alkali sites or alkali/copper interfaces, while CO₂ conversion is associated with unpromoted copper sites. This view reconciles many apparently contradictory results which have been reported in the literature.
Keywords: Chemical Engineering; Chemical Engineering